Shifting patterns of polyribosome accumulation at synapses over the course of hippocampal long‐term potentiation. Issue 6 (16th April 2018) - Ostroff, Linnaea E.; Watson, Deborah J.; Cao, Guan; Parker, Patrick H.; Smith, Heather; Harris, Kristen M.
Abstract: Hippocampal long‐term potentiation (LTP) is a cellular memory mechanism. For LTP to endure, new protein synthesis is required immediately after induction and some of these proteins must be delivered to specific, presumably potentiated, synapses. Local synthesis in dendrites could rapidly provide new proteins to synapses, but the spatial distribution of translation following induction of LTP is not known. Here, we quantified polyribosomes, the sites of local protein synthesis, in CA1 stratum radiatum dendrites and spines from postnatal day 15 rats. Hippocampal slices were rapidly fixed at 5, 30, or 120 min after LTP induction by theta‐burst stimulation (TBS). Dendrites were reconstructed through serial section electron microscopy from comparable regions near the TBS or control electrodes in the same slice, and in unstimulated hippocampus that was perfusion‐fixed in vivo. At 5 min after induction of LTP, polyribosomes were elevated in dendritic shafts and spines, especially near spine bases and in spine heads. At 30 min, polyribosomes remained elevated only in spine bases. At 120 min, both spine bases and spine necks had elevated polyribosomes. Polyribosomes accumulated in spines with larger synapses at 5 and 30 min, but not at 120 min. Small spines, meanwhile, proliferated dramatically by 120 min, but these largely lacked polyribosomes. The number of ribosomes per polyribosome is variable and may reflect differences in translation regulation. In dendritic spines, but not shafts, there were fewer ribosomes per polyribosome in the slice conditions relative to in vivo, but this recovered transiently in the 5 min LTP condition. Overall, our data show that LTP induces a rapid, transient upregulation of large polyribosomes in larger spines, and a persistent upregulation of small polyribosomes in the bases and necks of small spines. This is consistent with local translation supporting enlargement of potentiated synapses within minutes of LTP induction.